Comparative Analysis on Proteomics Profiles of Intracellular and Extracellular M.tb and BCG From Infected Human Macrophages - Liu, Han; Su, Li; Zhu, Tingting; Zhu, Xiaojie; Zhu, Yifan; Peng, Yonchong; Zhang, Kailun; Wang, Longwei; Hu, Changmin; Chen, Huanchun; Chen, Yingyu; Guo, Aizhen (Frontiers in Genetics, 2022)
Tuberculosis is the second cause in infectious diseases leading to human death. Understanding the virulence mechanism is inevitable if the disease needs to be fully cured. Therefore, this study aimed to reveal this mechanism by comparing proteomic profiles of intracellular and extracellular virulent strain M.tb and BCG from infected THP-1cells. First M.tb and BCG infected THP-1 at MOI 10:1. After 12 h postinfection, intracellular bacteria of M.tb and BCG were collected, while the two bacilli cultured in 7H9 broth media were used as the control. Then four groups of bacilli were subjected to proteomic analysis and differential proteomic profiles between M.tb and BCG were comparatively analyzed with bioinformatic tools. As a result, we identified a total of 1557 proteins. Further they were divided into four groups for comparison of M.tb vs. BCG under 7H9 culture (shorten as out), M.tb in (intracellular) vs. M.tb out, BCG in vs. BCG out and M.tb in vs. BCG in. Between M.tb in vs. BCG in, a total of 211 differentially expressed proteins were found. Eight proteins like ESAT-6 distributed in six RDs and some known proteins related to virulence. Besides, five uncharacterized proteins were differentially expressed. Further analysis revealed enriched pathways were associated with glyoxylate and dicarboxylate metabolism pathways. In M.tb out vs. BCG out, a total of 144 differential proteins were identified and mainly involved in metabolism pathways. Then 121 differential proteins in the group of M.tb in vs. M.tb out were enriched in ribosome and oxidative phosphsphorylation related to adaptation to the host environment. The group of BCG in vs. BCG out shared the same trend of different pathways to the M.tb in vs. M.tb out. Finally 42 proteins were identified to be up-regulated only in intracellular M.tb including eight RD proteins, while 22 up-regulated uniquely in intracellular BCG. Besides, only two proteins (Pks13 and Rv1405c) were commonly up-regulated in intracellular M.tb and BCG. Further, some unknown proteins were uniquely up-regulated in the intracellular M.tb and BCG. These findings provide valuable data for further exploration of molecular mechanism for M.tb virulence and BCG immune response.